Cryptocurrencies: technology, initiatives of banks and central banks, and regulatory challenges - Carvalho, Carlos Eduardo; Pires, Desirée Almeida [UNESP]; Artioli, Marcel [UNESP]; Oliveira, Giuliano Contento De (Instituto de Economia da Universidade Estadual de Campinas, 2021)
This paper analyses the impacts of the innovation known as distributed ledger technology (DLT) on the monetary system and on financial activities. Private cryptocurrencies, such as Bitcoin, are permissionless means of payment, based on blockchain, a form of DLT. Evaluations suggested that these private cryptocurrencies could compete with the banks payment systems and even supplant state currency. The development of these technologies has the potential to modify profoundly monetary and financial practices, but there are no indications that they may threaten the centrality of state money and the banking system in the contemporary monetary order. Major international banks have developed cryptocurrencies for settlement systems and for interbank transactions, including the so-called stablecoins, issued by highly technological companies with on par conversion into state money. Some central banks are studying the launch of state cryptocurrencies that could coexist with their fiduciary state currency and even replace their paper currency. The use of this technology results in new challenges for regulation, including the fact that cryptocurrencies can be used for money laundering and by organized crime.

O artigo analisa os impactos das inovações conhecidas como distributed ledger technology (DLT) sobre o sistema monetário e sobre as atividades financeiras. As criptomoedas privadas, como o bitcoin, são meios de pagamento de acesso livre, não permissionados, baseados na tecnologia blockchain, uma forma de DLT. Surgiram avaliações de que as criptomoedas privadas poderiam concorrer com os meios de pagamento bancários e com a moeda estatal, ou mesmo suplantá-la. O desenvolvimento destas tecnologias tem potencial para alterar intensamente as práticas monetárias e financeiras, mas não há indicações de que possam ameaçar a centralidade da moeda estatal e do sistema bancário na ordem monetária contemporânea. Grandes bancos internacionais têm desenvolvido criptomoedas para sistemas de liquidação de pagamentos e de transações interbancárias, inclusive as chamadas stablecoins, emitidas também por empresas de alta tecnologia, com paridade fixa com a moeda estatal. Bancos Centrais estudam o lançamento de criptomoedas próprias que possam conviver com sua moeda fiduciária e até substituir o papel-moeda. A aplicação desta tecnologia traz novos desafios para a regulação, inclusive porque criptomoedas podem ser utilizadas para lavagem de dinheiro e crime organizado.
Criptomoedas: tecnologia, iniciativas de bancos e de bancos centrais, desafios para a regulação
Keywords: Cryptocurrencies; Distributed ledger technology - DLT; Blockchain; Bitcoin; Regulation; Criptomoedas; Tecnologia de contabilidade distribuída - DLT; Blockchain, Bitcoin, Regulação